ASSOCIATION OF RENAL SAFETY PROFILE AND IMPACT OF ALBUMIN-TO-CREATININE RATIO OF DPP4 INHIBITORS COMPARED TO SULFONYLUREA IN DIABETIC KIDNEY DISEASE - Afreen Munir; Shahid Shoukkath Abdu; R. Ponraja; V. Lalitha (The Bioscan, 2024)
BACKGROUND: To analyze the potential impact of sulfonylurea (SU) and dipeptidyl peptidase-4 inhibitor (DPP4i) on the risk of significant renal events and the albumin to creatinine ratio in diabetic kidney disease. Here, were view the renal effects of DPP-4 inhibitors with special focus on its influence on the onset and progression of microalbuminuria by assessing albumin to creatinine ratio. We will discuss potential mechanism of these effects, the differences of action between sulfonylurea alone and addition of DPP-4 inhibitors to the treatment regimen, and future perspectives of its use in patients with diabetic kidney disease. The aim of this study was to determine the Reno protective effects of DPP-4i, using albumin to creatinine ratio and glomerular filtration rate (GFR) as indicators, in diabetic kidney disease. METHODS: In a single centre, an observational study was carried out and data from 120 patients were evaluated. The main factors that were evaluated utilizing case report form were the ADA diagnostic criteria, ACR (albumin to creatinine ratio), HbA1c value, and GFR (glomerular filtration rate). The investigation was conducted at the NG Hospital and Research Centre, Coimbatore. The study was carried out in the general medicine department and intensive care unit of the hospital over a period of 6 months from March 2023 to September 2023. CONCLUSION: DPP-4 inhibitors have a favorable effect profile, with minimal treatment-limiting adverse effects. These inhibitors are also known for their cardiovascular and renal safety, making them a preferred choice, particularly in patients with diabetes chronic kidney disease.Our study demonstrated that patients using DPP-4 inhibitors showed better outcomes compared to those using sulfonylurea alone for managing DKD.